Radiosynovectomy of the ankle in hemophilic arthropathy: effectiveness of samarium-153 and yttrium-90 - Hugo Maia Rodrigues; Giuliane Sarmet Moreira Damas dos Santos Portilho de Castro; Marcela dos Santos Martins; Mauro Cesar Mattos e Dinato; Glenda Feldberg Andrade Pinto; Janaina Bosso da Silva Ricciardi; Emerson Taro Inoue Sakuma; Allan de Oliveira Santos; Margareth Castro Ozelo; Rodrigo Gonçalves Pagnano (Journal of the Foot & Ankle, 2022)
Objective: Evaluate the effect of radiosynovectomy of the ankle with samarium-153 and yttrium-90 in hemophilic arthropathy through the possible reduction of hemarthrosis, analyzing complications, adverse effects, and the need for complementary therapies. Methods: Radiosynovectomy of the ankle in 15 hemophilic patients was analyzed retrospectively and followed between January 2008 and December 2021. The analysis was performed through patients’ medical records and diaries to quantify hemarthrosis that occurred six months before and six months after the procedure. Clinical follow-up and evaluation of outcomes were also analyzed. Results: Eighteen radiosynovectomies of the ankle were performed in 15 patients with a mean follow-up of 124 months. A reduction in episodes of haemarthrosis has been demonstrated within six months (p<0.001). There were no adverse effects or complications in the short and long term. Approximately 61.1% of the patients did not require complementary therapies afterward. Conclusion: The study demonstrated that radiosynovectomy of the ankle with samarium-153 and yttrium-90 in hemophilic patients is effective and safe. There was a decreased frequency of hemarthrosis, less need for complementary procedures, and no complications and adverse effects. Level of Evidence IV, Case Series.